Copper- and palladium-containing perovskites: Catalysts for the Ullmann and Sonogashira reactions - Lohmann, S; Andrews, S; Burke, B; Smith, M; Attfield, J; Tanaka, H; Kaneko, K; Ley, S (2005)
The utility of perovskite-based materials in organic synthesis is explored through examination of a series of copper- and palladium-containing perovskites in Ullmann and Sonogashira type reactions. La0.9Ce 0.1Co0.6Cu0.4O3 is identified as an effective catalyst for the synthesis of a range of biaryl ether and thioether functionalities, whilst a Cu- and Pd-containing perovskite is effective in the Sonogashira reaction. These results suggest that perovskites may be useful leads in the search for new catalysts and reagents for organic synthesis.